PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF GAMBAR TEKNIK BERBASIS SOFTWARE BANTU DI SUPM NEGERI BONE JURUSAN TEKNIKA PERIKANAN LAUT - Asriadi K; Nur Awaliah; Ahmad Afandi; Mawardi, Mawardi (Journal of Innovation Research and Knowledge, 2022)
This research and development aims at producing engineering drawing interactive learning media based on assistive software, examining the effectiveness of engineering drawing interactive learning media based on assistive software, describing the strengths and obstacles faced when engineering drawing interactive learning media based on assistive software is used. This research and development employed ADDIE model which consisted of 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The result of interactive multimedia development through expert validation and tryout stage has met the criteria of valid, practical, and effective. After being implemented to limited class, the result indicates that the students' learning completeness has met completeness standard, namely 91 > 80% or 31 out of 34 students have completed it. Based on the observation, teacher and students' activities and are in active categories. Based on the comparisons of learning result average of the previous batch students and the tryout subject students, it shows learning result improvement. Thus, the conclusion of the study is the interactive multimedia developed is effective and feasible to be used.